Presentation for Food Security and Agrifood Trade in Latin America and the Caribbean - Illescas, Nelson; Tejeda Rodriguez, Agustin (2023)
Intraregional food trade in the LAC region offers untapped opportunities for expansion. Currently, 60 percent of LAC food imports come from extraregional suppliers, despite a high degree of complementarity in the production of food products across LAC countries. Expanding LAC’s intraregional trade could improve access to, availability, and diversity of food, and ensure more stable food supplies in the face of growing risk of shocks, such as economic crises, extreme weather events, conflicts, and epidemics.